2009
DOI: 10.4049/jimmunol.0901431
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Pin1 Induction in Type II Collagen-Mediated Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation in joints and subsequent destruction of cartilage and bone. Inflammatory mediators such as PGs and proinflammatory cytokines contribute to RA progress. Pin1, a peptidyl prolyl isomerase, plays important pathophysiological roles in several diseases, including cancer and neurodegeneration. We found that both Pin1 and cyclooxygenase-2 (COX-2) were highly expressed in ankle tissues of type II collagen-induced RA mice. HTB-94 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 55 publications
1
30
0
1
Order By: Relevance
“…Up-regulation of PIN1 was also observed in radiation-exposed mouse skin tissues and JB6 Cl41 epidermal cells (Han et al 2011) and in chondrocytes, lymphocytes, and fibroblasts from RA lesions in mice with type II collagen-induced RA (Jeong HG et al 2009). Since PIN1 is up-regulated in periodontitis patients and nicotineand LPS-stimulated PDLCs, we evaluated PIN1 as a potential target for periodontitis.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Up-regulation of PIN1 was also observed in radiation-exposed mouse skin tissues and JB6 Cl41 epidermal cells (Han et al 2011) and in chondrocytes, lymphocytes, and fibroblasts from RA lesions in mice with type II collagen-induced RA (Jeong HG et al 2009). Since PIN1 is up-regulated in periodontitis patients and nicotineand LPS-stimulated PDLCs, we evaluated PIN1 as a potential target for periodontitis.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, NF-κB activation in PIN1-overexpressing chondrocytes is associated with overproduction of proinflammatory mediators in RA progression (Jeong HG et al 2009). It was recently reported that Pin1 -/-mice exhibit a defect in bone morphogenetic protein signaling in osteoblasts but normal osteoclast function (Shen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esnault et al (59) showed that juglone prevented acute and chronic rejection of MHC mismatched, orthotopic rat lung transplants by reducing the expression of IFN-␥ and CXCL-10 mRNA stability, accumulation, and protein expression after cell activation. Another report showed that juglone at a dose of 5 mg/kg can attenuate rheumatoid arthritis development and COX-2 expression in human primary cultured RA chondrocytes and in type II collagen (CII)-treated DBA/1J mice (60). In our study we injected juglone (3 mg/kg) intraperitoneally to C57BL/6 mice, which attenuated MPTP-induced expression of Pin1 in nigrostriatal axis (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We employed a known inhibitor of Pin1, juglone, to determine the neuroprotective efficacy of the compound in an established MPTP model of PD. Juglone (5-hydroxy-1,4-napthalenedione (C 10 H 6 O 3 )), an aromatic organic napthoquinone naturally found in the leaves, roots, and bark of black walnut plants, has been widely used as a Pin1 inhibitor (59,60). Juglone irreversibly inactivates enzymatic activity of human Pin1 by modification of thiol groups of cysteine residues (61).…”
Section: Discussionmentioning
confidence: 99%